Prophylactic immunoglobulin therapy in secondary immune deficiency – an expert opinion. (1st September 2016) - Agostini, Carlo; Blau, Igor-Wolfgang; Kimby, Eva; Plesner, Torben
ABSTRACT: Introduction : In primary immunodeficiency (PID), immunoglobulin replacement therapy (IgRT) for infection prevention is well-established and supported by a wealth of clinical data. On the contrary, very little evidence-based data is available on the challenges surrounding the use of IgRT in secondary immune deficiencies (SID), and most published guidelines are mere extrapolations from the experience in PID. Areas covered : In this article, four European experts provide their consolidated opinion on open questions surrounding the prophylactic use of IgRT in SID, based on their clinical experience. The main topics are IgRT initiation, route of administration, dose optimization, and therapy discontinuation. The authors hope this discussion will be of assistance to practicing physicians in their daily decision-making. Expert commentary : Although growing experience indicates that IgRT could play an important role in the management of SID, very little robust evidence is available to guide clinical practice. The authors stress the urgent need for new studies in the field and discuss points they find of importance to design them adequately.